Curative intent treatment in recurrent carcinoma cervix, numbers need to increase - Lamichhane, Deep; Suwal, Suraj; Baral, Shweta; Shrestha, Rishikesh Narayan (Nepalese Journal of Cancer, 2021)
Correction:  Due to an oversight three authors were omitted from this paper. On 27th January 2022, Suraj Suwal, Shweta Baral and Rishikesh Narayan Shrestha were added.Abstract: Cervical cancer is most common cancer among females in Nepal. Majority of them presents in advanced stage and treated with definitive chemo-radiation. Fifteen to thirty percent recurs and among them 50% are localised in pelvis. The only curative treatment available at this point is surgery in selected patients and total pelvic exenteration is most common operation performed among few other surgical options. First described almost 72 years back, now the morbidity and mortality of this so-called brutal procedure has decreased and this becomes the only hope of survival in these patients. We present a case of a person from remote village of Nepal who had recurrence following primary treatment and underwent total pelvic exenteration. She recovered well and is disease free at 1-year follow up and is treatment free. The aim of this case report is to create awareness among clinicians, patient and other person involved in cancer care that treatment with curative intent is still possible after cancer recurrence.